Transcriptome Analysis of Ovarian and Uterine Clear Cell Malignancies - Alldredge, Jill; Randall, Leslie; De Robles, Gabriela; Agrawal, Anshu; Mercola, Dan; Liu, Marisa; Randhawa, Pavneet; Edwards, Robert; McClelland, Michael; Rahmatpanah, Farah (Frontiers in Oncology, 2020)
Purpose: Ovarian and uterine clear cell carcinomas (CCCs) are rare, but associated with poor prognosis. This study explored RNA transcription patterns characteristic of these tumors. Experimental Design: RNA sequencing (RNA-seq) of 11 ovarian CCCs and 5 uterine CCCs was performed, and compared to publicly available data from high grade serous ovarian cancers (HGSOC). Ingenuity Pathway Analyses were performed. CIBERSORT analyses estimated relative fractions of 22 immune cell types in each RNA-Seq sample. Sequencing data was correlated with PD-L1 immunohistochemical expression. Results: RNA-seq revealed 1613 downregulated and 1212 upregulated genes (corrected p < 0.05, |FC|≥10) in ovarian CCC versus HGSOC. Two subgroups were identified in the ovarian CCC, characterized by ethnicity and expression differences in ARID1A. There were 3252 differentially expressed genes between PD-L1+/- ovarian CCCs, revealing immune response, cell death, and DNA repair networks, negatively correlated with PD-L1 expression, whereas cellular proliferation networks positively correlated with expression. In clear cell ovarian versus clear cell uterine cancer, 1607 genes were significantly upregulated, and 109 genes were significantly downregulated (corrected p < 0.05, |FC| ≥ 10). Comparative pathway analysis of late and early stage ovarian CCC revealed unique metabolic and PTEN pathways, whereas uterine CCC had unique Wnt/Ca+, estrogen receptor, and CCR5 signaling. CIBERSORT analysis revealed that activated mast cells and regulatory T cell populations were relatively enriched in uterine CCCs. The PD-L1+ ovarian CCCs had enriched resting NK cells and memory B cell populations, while PD-L1- had enriched CD8 T-cells, monocytes, eosinophils, and activated dendritic cells. Conclusions: Unique transcriptional expression profiles distinguish clear cell uterine and ovarian cancers from each other, and from other more common histologic subtypes. These insights may aid in devising novel therapeutics.